Fusarium co-infection in a patient of tubercular meningitis - Kaur, Ravinder; Panda, Pragyan S. (Journal of Neuroanaesthesiology and Critical Care, 2016)
Fusarium is a common soil fungus and it can cause serious illness in humans. Fusariosis is usually more invasive and disseminated in immune compromised individuals. We report a rare case of concomitant Fusarium meningitis in a patient with tubercular meningitis.
Keywords: Co-infection; Fusarium; tubercular meningitis